Literature as Antidote: Reflections on Don DeLillo’s Falling Man - el Moncef, Salah (International Journal of Humanities and Social Science Research, 2016)
This essay proposes an interpretation of Don DeLillo’s Falling Man based on a combination of textual analysis and contemporary theoretical approaches to the specific questions of trauma, grief, and posttraumatic healing as well as the more general question of the status of the subject in a postmodern context marked by increasing globalization and transnational interactions. This multidimensional interpretive approach makes it possible to theorize one of the central metanarrative questions posed by DeLillo’s novel: the potential function of the postmodern novel as an antidote against various expressions of contemporary angst, such as the dread of terrorist violence or the fear of aging and age-related maladies. In exploring the significance of a double esthetic articulation in DeLillo’s novel (an esthetic of estrangement and an “esthetic of disappearance”), the essay analyzes the author’s representation of his characters’ varying reactions to terror-related trauma and the role of the imagination in such reactions. While Falling Man represents subjective experiences of trauma and loss in painful and at times shocking ways, its dissection of the imaginary dimension of trauma also presents its readers with the possibility of incorporating various effects of traumatic experience into cohesive and constructive strategies of self-reassessment, grief management, and healing.